Coherent Power Combining of Four-Way Injection-Locked 5.8-GHz Magnetrons Based on a Five-Port Hybrid Waveguide Combiner - Huang, Heping; Yang, Bo; Shinohara, Naoki; Liu, Changjun (IEEE Transactions on Microwave Theory and Techniques, 2024)
A high-efficiency power-combining method for four-way 5.8-GHz magnetrons based on the external injection-locking technique is presented in this article. The method uses a nonisolated, lossless five-port hybrid waveguide combiner for power combining. Meanwhile, the injection-locking technology has been applied to magnetrons for achieving coherent power combining. The phase fluctuation of the injection-locked magnetron, without the presence of a phase-locked loop, measured nearly ±2.5°. In contrast, when a phase-locked loop was introduced, the phase fluctuation reduced significantly to approximately ±0.5°. This phase accuracy can fully meet the requirements of combining experiments. Four magnetrons worked in injection-locked states without phase-locked loop. The proposed power-combining system is designed, measured, and analyzed. Measurement results show that a high-power-combining efficiency of over 95% is achieved by injection-locked magnetron without PLL, with the best efficiency reaching up to 97.7% with phase control of the injected signals. Experimental results reveal that the magnetron phase-pushing effects and the ripple in high-power dc voltage and current have a minor impact of approximately 4% on the combining efficiency.